DIFFICULTIES OF PRINCIPALS WITH CARRYING OUT SCHOOL ACTION RESEARCH: A PHENOMENOLOGICAL ANALYSIS - Kistoro, Hanif Cahyo Adi; Roviana, Sri (UIN Sunan Kalijaga Yogyakarta, 2023)
Conducting research is important in supporting the development of an individual and institutional competencies. School action research is considered as a form of school improvement that can be undertaken by school principals. This research examines the difficulties school principals face with carrying out school action research and their impact. This research is a qualitative research design with a phenomenological approach. The participants in this study consisted of 11 school principals in the Special Region of Yogyakarta. Purposive sampling technique where participants were determined based on criteria, namely a school principal at one of the Muhammadiyah Elementary Schools in Yogyakarta Province who had served at least 4 years. Data collection was done through in-depth interviews and documentation. Data analysis used data reduction procedures, data presentation, and data interpretation. Data validity was carried out using source triangulation by cross-checking back to the informants regarding the questions and answers previously given. The findings of this research conclude that school action research should be carried out by school principals due to several factors. First, principals’ knowledge of research needs to be improved. Second, motivation for research should be improved. Third, School principals have not carried out much research due to lack of motivation. Fourth, there are age factors and physical and psychological fatigue, as well as a lack of supporting competence. Fifth, there is a lack of understanding of the benefits of research for schools and a lack of outreach and facilities in conducting research. This research still has limitations regarding research subjects, locations and designs. Future research could overcome the limitations of this study.